COMPARATIVE STUDY OF DOCUMENT TEXTS IN UZBEKISTAN AND TURKISH LANGUAGES (International journal of artificial intelligence, 2026)
The article provides a comparative analysis of the linguistic features of official document texts in the Uzbek and Turkish languages. The study studies the lexical, grammatical, syntactic and stylistic aspects of document texts, their normativeness and communicative function. The similarities and differences between Uzbek and Turkish document texts are identified, and their historical and linguistic reasons are revealed.